Hollow graphene microsphere loaded nano (Mg0. 2Co0. 2Ni0. 2Cu0. 2Zn0. 2) O and preparation method thereof
By depositing nano high-entropy oxide particles on the surface of hollow graphene microspheres, the problems of low electron conductivity and slow ion diffusion of rock salt-type high-entropy oxides are solved, and their rate performance and cyclic stability are significantly improved.
Patent Information
- Application Number
- CN202411853470.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The rock salt-type high-entropy oxide (Mg0.2Co0.2Ni0.2Cu0.2Zn0.2)O has low electron conductivity and slow ion diffusion, resulting in poor rate performance.
Using the preparation method of hollow graphene microspheres loaded nanometers (Mg0.2Co0.2Ni0.2Cu0.2Zn0.2)O, high-entropy oxide particles are deposited on the surface of hollow graphene microspheres through hydrothermal reaction to improve electron conductivity and ion diffusion ability.
The rate performance of rock salt-type high entropy oxide is significantly improved. The reversible specific capacity is close to 500mAh g-1 at 1A g-1 and 412mAh g-1 at 2A g-1, and good cycling stability is maintained.
Smart Images

Figure CN119695108A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical energy storage materials, and specifically relates to a hollow graphene microsphere loaded with nano (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O and preparation method. Background Art
[0002] The rapid development of electric vehicles has led to a growing demand for lithium-ion batteries with high energy density and long cycle life. In the past two decades, researchers have invested a lot of experience in developing new electrode materials with excellent performance. Among the various new negative electrode materials, conversion transition metal oxides (chemical formula M x O y , M=Fe, Co, Ni, Mn, V, etc.) have higher specific capacity than traditional embedded layered oxides and show great potential in high-energy lithium-ion battery applications. However, the huge volume change of transition metal oxides during the cycle will cause particle pulverization, resulting in rapid capacity decay, which is the key bottleneck restricting its practical application.
[0003] In recent years, the "high entropy" design concept has been applied in the research of positive and negative electrodes of lithium-ion batteries. The conversion reaction type metal oxide negative electrode improves the structural stability of the electrochemical process through the entropy stabilization structure strategy, thus proposing high entropy metal oxides (HEOs) negative electrode materials. HEOs are multi-principal solid solutions composed of five or more metal oxides. The local chemical environment of all metal cations is almost the same, and the metal elements are randomly distributed in the lattice. The high and stable configurational entropy makes HEOs exist in the form of single-phase compounds. The earliest studied rock salt type high entropy oxide negative electrode material (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O as an example, among which the electrochemically active Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Metal ions such as Mg provide capacity through conversion reactions, rather than active Mg 2+ It acts as a buffer matrix to stabilize the structure, inhibiting the agglomeration of active metal nanoparticles while allowing the ions involved in the reaction to easily diffuse back into the crystal structure during the subsequent oxidation process, thereby achieving good cycle stability.
[0004] However, rock salt type high entropy oxide (Mg 0.2 Co 0.2Ni 0.2 Cu 0.2 Zn 0.2 )O has low electronic conductivity and slow ion diffusion, resulting in poor rate performance. GHIGNAP et al. reported (ACS Applied Materials & Interfaces, 2020, 12: 50344-50354) that when the current density is 0.09A g -1 When (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O specific capacity is 600mAh g -1 However, if the current density is only increased to 0.1A g -1 When the reversible specific capacity is only 400 mAh g -1 The rock salt high entropy oxide (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O in 1Ag -1 At a current density of 1.34 W, the reversible specific capacity is 325 mAh g -1 (Materials Chemistry and Physics, 2021, 262). The rapid development of electric vehicles requires that the supporting lithium-ion batteries have not only high energy density but also a certain power density. Therefore, in order to realize the rock salt type high entropy oxide (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 In order to apply )O in high-energy lithium-ion batteries, it is necessary to study technical approaches to improve its rate performance.
[0005] For the conversion reaction mechanism (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O, and its rate performance improvement strategy mainly includes particle nano-sizing, porous structure and conductive material coating, so as to reduce the polarization effect in the reaction process, improve the kinetics, and finally achieve rate performance improvement. Summary of the invention
[0006] The purpose of the present invention is to improve the rock salt type (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn0.2 )O high entropy oxide negative electrode material rate performance, design a preparation method of hollow graphene microspheres loaded with nano high entropy oxide particles.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] In the first aspect, the present invention provides a hollow graphene microsphere loaded with nano (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O preparation method, specifically comprising the following steps:
[0009] (1) After fully grinding the graphite oxide dry powder, placing it in an inert gas atmosphere, heating it to 650-800° C. at a rate of 5-15° C. / min, keeping the temperature constant for 3-5 hours, and then naturally cooling it to room temperature to obtain a fluffy hollow graphene microsphere powder;
[0010] (2) cobalt (II) nitrate, magnesium (II) nitrate, copper (II) nitrate, zinc (II) nitrate and nickel (II) nitrate are weighed in an equal molar ratio of the metal elements, and pure water is added to prepare a mixed solution A with a total metal ion concentration of 0.005 to 0.01 g / mL; the prepared hollow graphene microsphere powder is prepared into a suspension B with a concentration of 0.005 to 0.02 g / mL using anhydrous ethanol;
[0011] (3) According to the hollow graphene microspheres and (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O has a mass stoichiometric ratio of 0.1:1 to 1:1, A and B are weighed separately, added into a hydrothermal reactor, and then ammonia water and urea are added; the hydrothermal reactor is placed at 130 to 150°C for sufficient reaction, and then naturally cooled to room temperature;
[0012] (4) Unscrewing the hydrothermal reactor to release the gas, collecting the solids, washing with pure water until the filtrate is neutral, drying the water and grinding to obtain a powder, then placing it in an inert gas, heating it from room temperature to 800-900°C at a rate of 3-5°C / min, and then keeping the temperature constant for 1-3 hours, and then cooling it naturally to room temperature to obtain hollow graphene microspheres loaded with nano (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O high entropy oxide powder.
[0013] Preferably, in step (1), the graphite oxide dry powder is synthesized by the Hummers method.
[0014] Furthermore, the graphite oxide dry powder is ball-milled at a rotation speed of 200-450 rpm for 2 hours, then raised from room temperature to 750° C. at a rate of 10° C. / min, maintained at a constant temperature for 3-5 hours, and then naturally cooled to room temperature.
[0015] Preferably, in step (3), the concentration of ammonia in the mixed solution after addition is 0.2-1%; the concentration of urea in the mixed solution after addition is 0.01-0.015 g / mL.
[0016] Preferably, in step (3), the mixed solution is added to a hydrothermal reactor with a volume of 100 mL, so that the volume of the mixed solution is in the range of 60 to 80 mL; and the reaction time is 3 to 6 hours.
[0017] Preferably, the inert gas is argon.
[0018] Preferably, the cobalt nitrate, magnesium nitrate, copper nitrate, zinc nitrate or nickel nitrate is replaced by other soluble salts of the same metal element.
[0019] In a second aspect, the present invention provides a hollow graphene microsphere loaded with rock salt type (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O composite materials.
[0020] Preferably, the hollow graphene microspheres are loaded with rock salt type (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O composite material particle size is 2.5-4 microns, the internal cavity diameter is 0.5-1 micron, and the surface of the graphene shell is in situ deposited with 100-200 nanometers of (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O high entropy oxide particles.
[0021] In a third aspect, the present invention provides a hollow graphene microsphere-loaded rock salt type (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O composite material as a negative electrode for lithium batteries. Preferably, the hollow graphene microspheres are loaded with nano rock salt type high entropy oxide (Mg 0.2 Co 0.2 Ni 0.2Cu 0.2 Zn 0.2 )O powder, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 7:2:1, and a slurry is prepared with nitrogen methyl pyrrolidone and coated on a copper foil, and then applied after drying.
[0022] Beneficial effects achieved by the present invention:
[0023] The button battery test shows that the hollow graphene microspheres loaded with rock salt type (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O high entropy oxide in 1Ag -1 The reversible specific capacity at the current density is close to 500 mAh g -1 , 2A g -1 412mAh g -1 Correspondingly, the (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O, not only is it a solid structure without pores, but also has a worse rate performance, 1A g -1 The reversible specific capacity is less than 200 mAh g -1 , 2A g -1 Moreover, the hollow graphene microspheres loaded with rock salt type (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 The first coulombic efficiency of the composite material (current density is 0.05A g -1 ) is 66.9%, which is higher than that of the pure (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O, while the hollow graphene microspheres loaded with rock salt type (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O at 1A g -1 After 700 cycles of current density, its specific capacity is still greater than 400 mAh g -1 , and also showed obvious capacity recovery effect.
[0024] The material preparation method of the present invention has the following characteristics: (1) the surface defects of the hollow graphene spherical shell can promote the formation of nano high entropy oxide particles; (2) the hollow graphene spherical shell can improve the electronic conductivity of the composite material; (3) the cavity of the graphene microsphere can store electrolyte, reduce the ion diffusion resistance, and thus improve the rate performance; (4) the synthesis method is simple and has high repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The SEM image of the hollow graphene microspheres loaded with rock salt type high entropy oxide prepared by the method of the present invention is
[0026] Figure 2 The cross-sectional FIB-SEM image of the hollow graphene microspheres loaded with rock salt type high entropy oxide prepared by the method of the present invention is
[0027] Figure 3 The element EDS image of the hollow graphene microspheres loaded with rock salt type high entropy oxide prepared by the method of the present invention is shown in FIG.
[0028] Figure 4 XRD diagram of hollow graphene microspheres loaded with rock salt type high entropy oxide prepared by the method of the present invention
[0029] In the figure: the ordinate is the diffraction intensity, the abscissa is the diffraction angle 2θ, the unit is °
[0030] Figure 5 The charge and discharge curves of hollow graphene microspheres loaded with rock salt type high entropy oxide prepared by the method of the present invention at different current densities
[0031] In the figure: the vertical axis is voltage, the unit is V, the horizontal axis is specific capacity, the unit is mAh / g
[0032] Figure 6 The results of 800 cycles of the hollow graphene microspheres loaded with rock salt type high entropy oxide prepared by the method of the present invention at 1A / g
[0033] In the figure: the vertical axis is the specific capacity, the unit is mAh / g, and the horizontal axis is the number of cycles, the unit is times.
[0034] Figure 7 For the unmodified rock salt type high entropy oxide negative electrode material (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O's first charge and discharge curve;
[0035] (a) 0.05A g -1 ; (b) 2A g -1 . DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0039] Example 1
[0040] (1) Weighing 1 g of graphite oxide prepared by the Hummers method, ball milling at a speed of 250 rpm for 2 hours, then placing it in argon, heating it from room temperature to 750° C. at a rate of 10° C. / min, keeping the temperature constant for 4 hours, and then naturally cooling it to room temperature to obtain a fluffy hollow graphene microsphere powder;
[0041] (2) Weighing 0.44 g of cobalt (II) nitrate hexahydrate, 0.38 g of magnesium (II) nitrate hexahydrate, 0.36 g of copper (II) nitrate trihydrate, 0.45 g of zinc (II) nitrate hexahydrate and 0.44 g of nickel (II) nitrate hexahydrate as synthetic raw materials, adding purified water to prepare a solution A with a metal ion concentration of 0.006 g / mL, a total of 67.8 mL, and using anhydrous ethanol to prepare a suspension B with a concentration of 0.01 g / mL of the prepared hollow graphene microsphere powder;
[0042] (3) Add the prepared solution A and suspension B into a 100 mL hydrothermal reactor, then add 2 mL of concentrated ammonia and 1 g of urea, tighten the lid of the reactor, place it in a 140° C. thermostat for 5 hours, and then cool it naturally to room temperature;
[0043] (4) Open the hydrothermal reactor to release the gas, collect the obtained solid, wash it with pure water until the filtrate is neutral, dry it in an oven at 80°C for 5 hours, grind it to obtain a powder, and then place it in argon gas and heat it from room temperature to 850°C at a rate of 4°C / min. After keeping the temperature constant for 2 hours, continue to pass argon gas and cool it to room temperature to obtain hollow graphene microspheres loaded with nano rock salt type high entropy oxide (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2Zn 0.2 )O powder.
[0044] Test results:
[0045] The prepared hollow graphene microspheres loaded with nano-rock salt type high entropy oxide (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O's morphology is shown in the attached Figure 1 -Attached Figure 3 、Phase analysis see attached Figure 4 , proving that its structural characteristics are: the main particle size is 3-4 microns, the loaded high entropy oxide (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O has a size of 100-200 nanometers and an internal cavity diameter of 0.5-1 micrometer.
[0046] The prepared hollow graphene microspheres were loaded with nano rock salt type high entropy oxide (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O powder, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 7:2:1, and slurry was prepared with nitrogen methyl pyrrolidone and coated on copper foil. After drying at 80 °C for 24 hours, the slurry was cut into 16 mm diameter discs. The cut discs were dried at 120 °C in vacuum for 4 hours, moved into an argon glove box, assembled with metal lithium sheets and 1M LiPF6EC / DEC (volume ratio 1:1) electrolyte into button batteries, and then LANHE CT3004A was used at 0.05A g -1 -2A g -1 The current range is tested;
[0047] The prepared hollow graphene microspheres loaded with nano rock salt type high entropy oxide 0.05Ag -1 -2A g -1 The charge and discharge curve and cycle life are shown in the attached Figure 5 -Attached Figure 6 , showing 2Ag -1 The reversible specific capacity is 412 mAh g -1 , is 0.05Ag -1 51% of the specific capacity at 1Ag -1 The reversible specific capacity during the 800 cycles was 500 mAh g -1 The reversible specific capacity of the 800th cycle exceeds 1200 mAh g-1 .
[0048] Comparative Example 1
[0049] The unmodified rock salt high entropy oxide (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O negative electrode material, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 7:2:1, and slurry was prepared with nitrogen methyl pyrrolidone and coated on copper foil. After drying at 80°C for 24 hours, the slurry was cut into 16 mm diameter discs, which were dried in a vacuum at 120°C for 4 hours, moved into an argon glove box, assembled with metal lithium sheets and 1M LiPF6 EC / DEC (volume ratio 1:1) electrolyte into button batteries, and then LANHE CT3004A was used in 0.05-2Ag -1 The current range is tested;
[0050] Unmodified rock salt high entropy oxide anode material at 0.05A g -1 The first charge and discharge curves of 2Ag -1 The charge and discharge curves are as follows Figure 7 As shown. At 0.05Ag -1 During the first charge and discharge process, its first coulombic efficiency was 62.07% and its first reversible specific capacity was 497.3 mAh g -1 ; In 2Ag -1 Its reversible specific capacity is 103.4 mAh g -1 .
[0051] Based on the experimental data of Example 1 and Comparative Example 1, the hollow graphene microspheres prepared by the method loaded with rock salt type high entropy oxide negative electrode material (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O has excellent rate performance and cycle stability, reaching the advanced level of similar materials.
Claims
1. A hollow graphene microsphere loaded with nano (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O preparation method, characterized in that, The specific steps include: (1) After fully grinding the graphite oxide dry powder, placing it in an inert gas atmosphere, heating it to 650-800° C. at a rate of 5-15° C. / min, keeping the temperature constant for 3-5 hours, and then naturally cooling it to room temperature to obtain a fluffy hollow graphene microsphere powder; (2) cobalt (II) nitrate, magnesium (II) nitrate, copper (II) nitrate, zinc (II) nitrate and nickel (II) nitrate are weighed in an equal molar ratio of the metal elements, and pure water is added to prepare a mixed solution A with a total metal ion concentration of 0.005 to 0.01 g / mL; the prepared hollow graphene microsphere powder is prepared into a suspension B with a concentration of 0.005 to 0.02 g / mL using anhydrous ethanol; (3) According to the hollow graphene microspheres and (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O has a mass stoichiometric ratio of 0.1:1 to 1:1, A and B are weighed separately, added into a hydrothermal reactor, and then ammonia water and urea are added; the hydrothermal reactor is placed at 130 to 150°C for sufficient reaction, and then naturally cooled to room temperature; (4) Unscrewing the hydrothermal reactor to release the gas, collecting the solids, washing with pure water until the filtrate is neutral, drying the water and grinding to obtain a powder, then placing it in an inert gas, heating it from room temperature to 800-900°C at a rate of 3-5°C / min, and then keeping the temperature constant for 1-3 hours, and then cooling it naturally to room temperature to obtain hollow graphene microspheres loaded with nano (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O high entropy oxide powder.
2. The hollow graphene microspheres loaded with nanoparticles (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O preparation method, characterized in that, In the step (1), the graphite oxide dry powder is synthesized by the Hummers method.
3. according to claim 2 the hollow graphene microsphere load nano (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O preparation method, characterized in that, The graphite oxide dry powder is ball-milled at a rotation speed of 200-450 rpm for 2 hours, then raised from room temperature to 750° C. at a rate of 10° C. / min, kept at a constant temperature for 3-5 hours, and then naturally cooled to room temperature.
4. The hollow graphene microspheres loaded nanometer (Mg according to claim 1 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O preparation method, characterized in that, In the step (3), the concentration of ammonia in the mixed solution after being added is 0.2-1%; the concentration of urea in the mixed solution after being added is 0.01-0.015 g / mL.
5. according to claim 1 the hollow graphene microsphere load nano (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O preparation method, characterized in that, In the step (3), the mixed solution is added into a hydrothermal reaction kettle with a volume of 100 mL, so that the volume of the mixed solution is in the range of 60 to 80 mL.
6. The hollow graphene microsphere-loaded nanoparticles (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O preparation method, characterized in that, The inert gas is argon.
7. The hollow graphene microsphere-loaded nanoparticles (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O preparation method, characterized in that, The cobalt nitrate, magnesium nitrate, copper nitrate, zinc nitrate or nickel nitrate is replaced by other soluble salts of the same metal element.
8. A hollow graphene microsphere loaded with rock salt type (Mg) prepared by the method according to any one of claims 1 to 7 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O composite materials.
9. A hollow graphene microsphere loaded with rock salt type (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O composite materials as negative electrodes for lithium-ion batteries.
10. The hollow graphene microspheres prepared by the method according to claim 9 are loaded with rock salt type (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O composite material is characterized by: The hollow graphene microspheres loaded with rock salt type (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 The particle size of the composite material is 2.5-4 microns, the internal cavity diameter is 0.5-1 micron, and the surface of the graphene shell is in situ deposited with 100-200 nanometers of (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O high entropy oxide particles.
Citation Information
Patent Citations
Preparation method and application of nano(Mg0.2Co0.2Ni0.2Cu0.2Zn0.2)O
CN108682840A
High-entropy alloy nanocomposite material and preparation method thereof
CN112746213A
Carbon-based pentabasic high-entropy alloy NiCuZnCdIn material as well as preparation method and application thereof
CN115275160A
Self-supporting high-entropy oxide / graphene composite material as well as preparation method and application thereof
CN115911299A
Hybrid Graphene Composite Particles
KR102545573B1